1992
DOI: 10.1007/bf00572829
|View full text |Cite
|
Sign up to set email alerts
|

Alginate coating of islets of Langerhans: in vitro studies on a new method for microencapsulation for immuno-isolated transplantation

Abstract: Immuno-isolated transplantation offers the attractive prospect of being able to transplant xenogeneic islets without immunosuppression. This study introduces a completely new method of coating single islets using a homogeneous alginate membrane approximately 10 microns thick. During glucose challenge (perifusion and static incubation) encapsulated islets show the same pattern and quantity of insulin release as non-encapsulated controls. This encapsulation method markedly reduces the amount of transplanted mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…We cannot fully explain why these simple capsules work so well for islet xenografts. Previous studies have shown that barium cross-linkage provides stronger alginate gels than those found with calcium (23). In addition, the avoidance of PLL is probably helpful because the macrophage activation so often seen with PLL might act synergistically with a xenograft reaction.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot fully explain why these simple capsules work so well for islet xenografts. Previous studies have shown that barium cross-linkage provides stronger alginate gels than those found with calcium (23). In addition, the avoidance of PLL is probably helpful because the macrophage activation so often seen with PLL might act synergistically with a xenograft reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate is the most commonly used material [119] [120]. Many divalent cations including CaCl 2 and BaCl 2 can produce crosslinking of alginate and the degree of crosslinking varies depending on the cation type [120].…”
Section: Therapeutic Actions Of Cells Encapsulatedmentioning
confidence: 99%
“…In encapsulated cells that are implanted as a therapy for diseases such as Type I Diabetes, transport of nutrients and active components (e.g. insulin) must not be hindered, while that of immuno-system agents must be suppressed [11,12,[18][19][20][21][22]. One way of obtaining such selectivity is by controlling surface porosity, namely, the dimensions of the pores through which transport of the diffusants occurs.…”
Section: Introductionmentioning
confidence: 99%